Citreicella manganoxidans sp nov., a novel manganese oxidizing bacterium isolated from a shallow water hydrothermal vent in Espalamaca (Azores) - Rajasabapathy, Raju; Mohandass, Chellandi; Dastager, Syed Gulam; Liu, Qing; Li, Wen-Jun; Colaco, Ana (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2015)
A Gram-stain negative, non-motile, non-spore forming, aerobic and rod or narrow lemon-shaped bacterial strain, VSW210(T), was isolated from surface seawater in a shallow water hydrothermal vent region in Espalamaca (Azores). Strain VSW210(T) was found to grow optimally at 30 A degrees C, at pH 7 and in the presence of 2-6 % (w/v) NaCl. A neighbour-joining phylogenetic tree based on 16S rRNA gene sequences revealed that strain VSW210(T) clusters with the type strain Citreicella marina CK-I3-6(T) (sequence similarity value of 99.6 %), but DNA-DNA hybridization showed DNA-DNA relatedness between the strain VSW210(T) and C. marina CK-I3-6(T) to be 55.8 +/- A 3.2 %. The DNA G+C content of strain VSW210(T) was determined to be 67.4 mol%. The cellular fatty acid profiles of strain VSW210(T) was found to contain C-18:1 omega 7c (80.1 %) and C-16:0 (9.2 %). The major polar lipids in strain VSW210(T) were identified as phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, diphosphatidylglycerol and an unidentified phospholipid. Strain VSW210(T) was found to be able to oxidize soluble Mn(II) to insoluble MnO2, which was confirmed with LBB staining. Differential phenotypic properties and genetic uniqueness revealed that this strain VSW210(T) is distinguishable from other species of the genus Citreicella. On the basis of the data presented, strain VSW210(T) is considered to represent a novel species of the genus Citreicella, for which the name Citreicella manganoxidans sp. nov. is proposed. The type strain is VSW210(T) (=KCTC 32497(T) = MCC 2286(T)).
Keywords: Azores; Citreicella manganoxidans sp nov; Hydrothermal vent; Polyphasic taxonomy; Seawater